The role of water resources in tourism development in Halsho district (Raparin Journal of Humanities (RJH), 2024)
Water is considered one of the most important requirements of life and is the source of life. It has been given an important place in the map and policies of states in today's world. Water is also an important tool for policy, economic, and demographic mapping. There is no doubt that the water consumption center will develop in the future and the population's demand for water will increase. With the development of civilization, industry, and modern life, water plays an important role in the emergence and development of the most important economic activity of the population today. This study is dedicated to identifying the impact between water resources and tourism activities in Halsho district. The importance of this research is that it presents the relationship and impact of water resources on tourism activities in a scientific and detailed manner through the use of several maps to illustrate the relationship between this natural resource and tourism activities. The main objectives of this research are to highlight the role of water resources in how to develop tourism and to discuss a new and modern mechanism for further benefits of water resources in Halsho district.This research consists of three main parts: the first is about water resources in the sub-district, which discusses the surface and groundwater resources of the study area; the second part is about the concept of development, and its types and principles for tourism in Halsho Sub-district are presented. We have reached several conclusions from this study, including:1- Halsho sub-district is one of the areas that are rich in groundwater resources, and the Saraw of Halsho springs has become the basis for the creation of tourist areas and attracts tourists.2- The appearance and existence of several tourist areas in Halsho sub-district indicate that the study area is moving towards tourism, because only in the center of the sub-district there are about 16 tourism projects and 191 tourism bowers.Finally, several suggestions and recommendations are presented in order to develop the tourism sector in Halsho sub-district.